Fundamentação, decisão judicial e argumentação: uma análise da teoria de Manuel Atienza na ADI 4439 STF - Posses, Bruna Pereira das (2019)
The Constitution of the Republic promulgated in 1988 in order to achieve its democratic proposal has brought, among many others, the right of substantiation of legal decisions. This right is revealed in the determination of the Judiciary when pronounce its decisions, substantiate well, to be ensure that the courts understand the reasons that led to such position, allowing the court disagree or even controlling it. Thereby, in this paper analyses, which elements should restrain in a legal proviment in order to assure that is sufficiently substantiate, achieving the constitutional and infraconstitutional determinations. It was pointed out that the argumentation is a fundamental part of this principle, and that the Legal Argumentation Theory proposed by Manuel Atienza provides interesting guidelines to the Judges make a legitimate decision. Looking for the apply the theory explained in the research, an analysis was made of a concrete situation: ADI 4439 judged by the STF in 2017, in which there was supposedly a conflict between the Brazilian State's option for laicity and the religious freedom, analyzed within of the constitutional determination of the existence of the discipline of religious education in public elementary schools. It was demonstrated, through the deductive method, with well-defined criteria of interpretation (the criteria proposed by Manuel Atienza for the evaluation of arguments), that is not always that a decision will be made with arguments considered “good”, and that in the case of collegial judgments , the subdued thesis may contain "better" elements than the winner. This exists, because, the judges do not only receive cases whose solution depends solely on the subsumption of fact to the norm, but demands permeated by a complex issues and values (as ADI 4439), demonstrating that the question of the existence, or not of a single correct answer in the law, is highly controversial. It was concluded that regardless of whether or not there is a single correct answer, law enforcers should make their statements and grounds have a fully meaning, searching the intend that their answer is the only able, and it is impossible to dissociate from such practice the use of good legal argumentation.